Is the sedimentation sign associated with spinal stenosis surgical treatment effect in SPORT? - Moses, R.; Zhao, W.; Staub, L.; Melloh, Markus; Barz, T.; Lurie, J. (2015)
STUDY DESIGN: Subgroup analysis of the lumbar spinal stenosis (LSS) without degenerative spondylolisthesis diagnostic cohort of the Spine Patient Outcomes Research Trial multicenter randomized clinical trial with a concurrent observational cohort. OBJECTIVE: To determine if sedimentation sign on magnetic resonance image can help with LSS treatment decisions. SUMMARY OF BACKGROUND DATA: LSS is one of the most common reasons for surgery in the US elderly, but there is a dearth of reliable diagnostic tools that give a clear indication for surgery. Recent studies have suggested that positive sedimentation sign on magnetic resonance image may be a possible prognostic indicator. METHODS: All patients with LSS in both the randomized and observational cohorts had imaging-confirmed stenosis, were surgical candidates, and had neurogenic claudication for at least 12 weeks prior to enrollment. Patients were categorized as "mild," "moderate," or "severe" according to stenosis severity. Of the 654 patients with LSS enrolled in Spine Patient Outcomes Research Trial, complete T2-weighted axial and sagittal digitized images of 115 patients were available for retrospective review. An independent orthopedic spine surgeon evaluated these deidentified Digital Imaging and Communications in Medicine files for the sedimentation sign. RESULTS: Sixty-six percent (76/115) of patients were found to have a positive sedimentation sign. Those with a positive sedimentation sign were more likely to have stenosis at L2-L3 (33% vs. 10% P=0.016) or L3-L4 76% vs. 51%, P=0.012), and to have severe (72% vs. 33%, P<0.0001) central stenosis (93% vs. 67% P<0.001) at 2 or more concurrent levels (57% vs. 18%, P=0.01). In multivariate models, the surgical treatment effect was significantly larger in the positive sedimentation sign group for Oswestry Disability Index (-16 vs. -7; P=0.02). CONCLUSION: A positive sedimentation sign was associated with a small but significantly greater surgical treatment effect for Oswestry Disability Index in patients with symptomatic LSS, after adjusting for other demographic and imaging features. These findings suggest that positive sedimentation sign may potentially be a useful adjunct to help guide an informed treatment choice regarding surgery for LSS. LEVEL OF EVIDENCE: 2.